2013
DOI: 10.1007/s00109-013-1075-4
|View full text |Cite
|
Sign up to set email alerts
|

The ACMSD gene, involved in tryptophan metabolism, is mutated in a family with cortical myoclonus, epilepsy, and parkinsonism

Abstract: Familial cortical myoclonic tremor and epilepsy is a phenotypically and genetically heterogeneous autosomal dominant disorder characterized by the presence of cortical myoclonic tremor and epilepsy that is often accompanied of additional neurological features. Despite the numerous familial studies performed and the number of loci identified, there is no gene associated with this syndrome. It is expected that through the application of novel genomic technologies, such as whole exome sequencing and whole genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 33 publications
(44 reference statements)
1
53
0
Order By: Relevance
“…Moreover, not only GABA A but additional other neurotransmitters have been implicated in the pathogenesis of CM. A recent mutation of the A‐amino‐β‐carboxymuconate‐ε‐semialdehyde decarboxylase (ACMSD) gene has been identified in one family with FCMTE . The enzymic product of ACMSD is involved in tryptophan metabolism via the kynurenine pathway, implicating more metabolites in the pathogenesis of CM .…”
Section: Inhibitory Neurotransmissionmentioning
confidence: 99%
“…Moreover, not only GABA A but additional other neurotransmitters have been implicated in the pathogenesis of CM. A recent mutation of the A‐amino‐β‐carboxymuconate‐ε‐semialdehyde decarboxylase (ACMSD) gene has been identified in one family with FCMTE . The enzymic product of ACMSD is involved in tryptophan metabolism via the kynurenine pathway, implicating more metabolites in the pathogenesis of CM .…”
Section: Inhibitory Neurotransmissionmentioning
confidence: 99%
“…This assumption is further supported by the identification of ACMSD common genetic variability in other polymorphisms as a risk factor for PD by numerous different groups, the identification of an ACMSD null mutation, not previously reported, in a family with a complex neurological phenotype including parkinsonism, and the low frequency of our reported mutation in public databases (8.146E-06). The fact that our patient carrying the p.Glu298Lys missense mutation in the ACMSD gene had a milder phenotype than the family reported with the ACMSD p.Trp26Stop mutation [5], a stop codon mutation, may be related to the type of mutation. Some nonsense, frameshift, or deletions in movement disorders genes, such as those in DNAJC6 and SYNJ1 genes, are associated with more severe phenotype than missense mutations in the same genes.…”
Section: Discussionmentioning
confidence: 59%
“…Although common genetic polymorphisms in the vicinity of the ACMSD gene were previously shown to be associated with increased risk for PD by several GWAS studies [1][2][3][4], we know of no reports on specific mutation in this gene in patients with sporadic PD. Recently, a stop codon ACMSD mutation (p.Trp26Stop) has been reported in a family with cortical myoclonus, epilepsy, and parkinsonism [5]. In this family affected members suffered from seizures and postural hand tremor.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although their study did not find clear mutations in the coding region of the CSMD3 gene, they found 24 possible single nucleotide polymorphisms, including 18 new polymorphic sites. [12,13] But according to reports, the association between the CSMD3 and ACMSD genes and familial FCMTE patients in China has rarely been reported. In future studies, rather than treating the CSMD3 and ACMSD genes as two independent entitites, we will study the two genes together and discuss the site at which CSMD3 and ACMSD genes exist in linkage relationship in FCMTE.…”
Section: Discussionmentioning
confidence: 99%